(untitled) (The Pakistan Development Review, 1995)
Realising productivity gains in agriculture is an important challenge for Pakistan. With a fast-growing population (3.1 percent per year), it is difficult for the economy to meet domestic food requirements. Like most less developed countries, yields of most crops in Pakistan are lower than the yields realised by researchers in on-farm experiments conducted in the farmers’ fields. The average yield gap between the farmers’ current yields and what would be profitable and feasible, given existing technology, is reported to be 30 to 40 percent [Byerlee (1987)]. Byerlee (1987), however, suggests that there is a potential for increasing productivity in most of the irrigated areas of Pakistan through the use of new inputs and a more efficient use of the existing inputs to exploit the genetic potential of the existing varieties. He argues that the wide array of new inputs vastly increases the complexity of crop management.1 The technical skills required to use the new inputs efficiently are much greater than the simple skills needed to adopt varietal changes. Hence, with more complex technological options and a more dynamic environment, the potential for economic inefficiency (both technical and allocative) is substantially increased. The purpose of this paper is to measure farm-specific allocative efficiency and the effect of management variables on allocative efficiency of wheat producers in an irrigated area in northern Pakistan.2 This will assist researchers, extension agents, and policy-makers to identify the ways and means to increase wheat productivity in Pakistan.